2018
DOI: 10.15294/higeia.v2i2.18854
|View full text |Cite
|
Sign up to set email alerts
|

Kinerja Petugas Surveilans Kesehatan dalam Upaya Penanggulangan Demam Berdarah Dengue

Abstract: Gasurkes is a manifestation of the larva monitoring officers (PPJ) as mentioned in Local Regulation No 5 Year 2010. Gasurkes are assigned since january 2nd, 2015 in Semarang. Gasurkes works facilitator in solving problems of DHF by means of inspection larva on houses, schools, islamic boarding schools, worship places, and other buildings, and in providing information about DHF in which it aims to reduce the number of DHF case in Semarang. After Gasurkes was formed, IR and CFR of DHF in Tembalang District, espe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…15 Ketersediaan sarana untuk program surveilans akan berdampak terhadap berjalannya program surveilans namun keterbatasan pendanaan juga akan berdampak terhadap perbaikan dan pengadaan sarana yang rusak. 23 Kepemilikan sarana berupa teknologi seperti software akan mempercepat penurunan penularan Covid-19 dengan berjalannya surveilans Covid-19 melalui software pencatatan dan pelaporan. 24 Sarana dan prasarana menjadi salah satu faktor yang penting dalam pelaksanaan program surveilans.…”
Section: Saranaunclassified
“…15 Ketersediaan sarana untuk program surveilans akan berdampak terhadap berjalannya program surveilans namun keterbatasan pendanaan juga akan berdampak terhadap perbaikan dan pengadaan sarana yang rusak. 23 Kepemilikan sarana berupa teknologi seperti software akan mempercepat penurunan penularan Covid-19 dengan berjalannya surveilans Covid-19 melalui software pencatatan dan pelaporan. 24 Sarana dan prasarana menjadi salah satu faktor yang penting dalam pelaksanaan program surveilans.…”
Section: Saranaunclassified
“…Research [26] focuses on analyzing the performance of Gasurkes in efforts to tackle DHF in endemic villages, where the results of the study showed that Gasurkes's knowledge was not good, there were good perceptions, lack of motivation, not yet enforced rewards, support of socioeconomic and political environment that was not optimal, the leadership process that has not been optimal, the workload that has not been evenly distributed, insufficient labor and sufficient facilities. The conclusion of the research shows that the performance of Gasurkes in the efforts to overcome DHF in endemic villages is not optimal.…”
Section: Introductionmentioning
confidence: 99%